An exploratory study of unexplained concentration of 18F-PSMA-1007 in the bladder for prostate cancer PET/CT imaging - Dang, Jun; Yao, Yutang; Li, Yingchun; Tan, Xiaofei; Ye, Zhenyan; Zhao, Yi; Qing, Shiwei; Kou, Ying; Jiang, Xiao; Lu, Hao; Chen, Shirong; Zhao, Meng; et al. (Frontiers in Medicine, 2023)
18F-PSMA-1007 PET/CT imaging is increasingly used for the diagnosis, staging, and efficacy assessment of patients with prostate cancer. Compared with other PSMA tracers, 18F-PSMA-1007 is mainly cleared by the liver and bile and has lower urinary clearance, thus allowing a better assessment of the lesions around the bladder. However, there were some patients who showed an obvious concentration of the 18F-PSMA-1007 in the bladder, which may affect the observation of peripheral lesions, but the mechanism of this change is unknown. The aim of this study was to explore the cause of bladder 18F-PSMA-1007 concentration by assessing the clinical and imaging characteristics of 18F-PSMA-1007 PET/CT scans. A total of 284 patients were included in this retrospective study, and their clinical characteristics such as age, height, weight, Gleason score, metastases, different treatment methods, the level of liver and kidney function, PSA level, and imaging characteristics such as 18F-PSMA-1007 injected activity, the interval between injection to scan, physiological distribution (parotid gland, kidney, liver, spleen, intestine, obturator internus), pathological distribution (prostate lesions, metastases) were collected, and were compared after subgrouping using bladder urine SUVmax. This study showed that the distribution of bladder 18F-PSMA-1007 was not correlated with the above clinical and imaging characteristics, so further studies are needed to find the explanations， and thus to improve the disease assessment of this type of prostate cancer patients.